A follow-up study of patients with Dhat syndrome: Treatment pattern, outcome, and reasons for dropout from treatment - Grover, Sandeep (Indian J Psychiatry, 2016)
AIM: The aim of this study was to evaluate the treatment pattern and satisfaction with treatment provided to patients with Dhat syndrome. It was also aimed to study the follow-up rates and reasons for dropping out of treatment in patients with Dhat syndrome. MATERIALS AND METHODS: Sixty-four subjects diagnosed with Dhat syndrome were prospectively contacted to evaluate treatment satisfaction and reason for dropout after 6 months of baseline evaluation. Sociodemographic, clinical details were recorded at initial intake and Sex Knowledge and Attitude Questionnaire was applied. After 6 months, information on treatment received, number of follow-up visits to the clinic and the outcome were extracted from the treatment records. Treatment satisfaction using Patient Satisfaction Questionnaire and reasons for dropping out from treatment were assessed by a telephonic interview. RESULTS: Twenty-three patients were categorized as treatment completers, 14 as early drop-outs and 27 as late drop-out. The mean (standard deviation) number of visits over the period of 6 months was 3.81 (3.06). The outcome at 6 months was no change in 45.3%, improved in 32.8% and recovered in 21.9%. Higher proportion of treatment completers (52.2%) sought psychiatric help on their own compared to those who dropped out early from the treatment (7.1%). Treatment completers had better knowledge, and more positive attitude toward sex compared to late drop-out group. 34.4%of the subjects were fully satisfied with the various components of treatment. Level of satisfaction was highest for treatment completers. The most common reasons given by those who dropped out early were “not able to spare time for consultation” (21.4%) and “not prescribed medications” (21.4%). The most common reason given by those belonging to “late drop-out” group was ‘no improvement with treatment in symptoms of Dhat syndrome (40.7%). CONCLUSIONS: Patients with Dhat syndrome frequently drop-out of the treatment network. There is a need to reorganize the services for these patients and understand their expectations from the treatment so as to provide better care.